تطوير متحكم مرتكز على الشبكات العصبونية الصنعية ذات التغذية الأمامية وعلى طريقة التحكم المباشر لتحسين كفاءة نظم الطاقة الشمسية الكهروضوئية باستخدام Matlab/Simulink - ديلانة إيمان (Latakia University Journal -Engineering Sciences Series, 2018)
يقدم البحث منهجية جديدة لتطوير متحكم مرتكز على الشبكات العصبونية الصنعية ANN وعلى طريقة التحكم المباشر، بهدف الحصول على الطاقة القصوى الممكنة من النظم الشمسية الكهروضوئية في ظل التغيرات الجوية المختلفة من شدة إشعاع شمسي ودرجة حرارة محيطة. في هذا السياق، يقدم البحث نموذج جديد لمتحكم MPPT-ANN لتتبع نقطة الاستطاعة العظمى MPP للنظم الشمسية الكهروضوئية في بيئة Matlab/Simulink. يرتكز المتحكم MPPT-ANN المطور على شبكة عصبونية صنعية ذات تغذية أمامية FFNNمدربة باستخدام خوارزمية الانتشار العكسي للخطأ، لتحديد توتر التشغيل الأمثل للنظام الكهروضوئي PV عند التغيرات الجوية المختلفة. كما يقترح البحث، خوارزمية تحكم تعتمد على طريقة التحكم المباشر لتحديد نسبة التشغيل المستخدمة للتحكم مباشرة في دورة عمل مبدل جهد مستمر، وذلك اعتماداً على مقارنة الفرق الناتج بين توتر خرج النظام الكهروضوئي وتوتر التشغيل الأمثل خرج الشبكة العصبونية. إن لمتحكم المطورMPPT-ANN المرتكز على شبكة FFNN، يمتاز بسرعة فائقة بتتبع نقطة MPP وبتحقيق كفاءة عالية لنظام PV عند التغيرات الجوية. أظهرت نتائج المحاكاة المنجزة في بيئة Matlab/Simulink، الأداء الأفضل للمتحكم المطور MPPT-ANN بتحقيق أداء ديناميكي أفضل ودقة عالية عند تتبع نقطة MPP، مقارنة مع استخدام متحكم أخر MPPT-ANN-PI يعتمد على شبكة عصبونية صنعية ومتحكم تناسبي-تكاملي تقليدي، ومقارنة أيضا ً مع متحكم تقليدي MPPT-P&O مرتكز على تقنية الاضطراب والمراقبة عند التغيرات الجوية المختلفة. This research presents a new methodology for the development of a controller based on Artificial Neural Networks and Direct control method in order to obtain the maximum available energy from Solar Photovoltaic (PV) Energy systems under different atmospheric changes of the solar insolation and ambient temperature. In this context, this research presents a new model for MPPT-ANN in order to track the Maximum Power Point of PV systems in Matlab/Simulink environment. The developed controller is based on Feed Forward Neural Network FFNN trained by Back-propagation algorithm of error to determine the optimal voltage operation of the system PV system at different atmospheric changes. This research also suggests, control algorithm based on the direct control method in order to determine the duty cycle, which used to control directly the operating of DC-DC Voltage Converter, depending on a comparison of the difference between the output voltage of PV system and the optimal voltage output of the neural network. The developed controller MPPT-ANN based on a network FFNN, Characterized by fast speed to track of MPP point and achieve high efficiency for the PV system under the atmospheric changes. The simulation results completed in Matlab/Simulink environment, showed the best performance of developed controller MPPT-ANN by achieving a better dynamic performance and high accuracy when tracking the MPP, compared with the use of the another PI-ANN controller based on artificial neural network and the conventional Proportional-Integral Controller, and compared with the use of the conventional MPPT-P&O based on Perturb and Observe (P&O) technique under different atmospheric changes.